Using graphic organizer in helping year five pupils to comprehend the small 'I' - Hiew, Mei Ping (2010)
Graphic organizers are structural tools that help readers organize thoughts. By using graphic organizers, pupils can experience words beyond pronunciation and display connections between ideas and concepts to improve comprehension. Graphic organizers help pupils sort, show relationship, make meaning, and manage data quickly and easily before, during, and after reading and discussion. As a result, pupils can display connections between ideas and concept, thus improving the text comprehension. The subjects were primarily Year Five pupils (n = 60) at a suburban school in Kota Kinabalu. The purpose of this study was to examine the effectiveness of using graphic organizers as a learning tool to help Year Five pupils organize thoughts and improve reading comprehension. Using a triangular approach to data collection, this 6 week study utilized a Pre-test and Post-test control group design and individual interviews to determine the effects of graphic organizers on pupils' achievement. The data suggests that using graphic organizers might have been one factor that aided pupils in the reading comprehension process. In addition, 'this study revealed that pupils believed that graphic organizers were helpful in allowing them to organize their thoughts after reading a story. A paired samples t - test determined significant difference in achievement between the groups. The experimental group improved in achievement at least as much as the control group